Molecular dynamics simulation of shear friction process in tectonically deformed coal - Liu, Hewu; Song, Yu; Du, Zhigang (Frontiers in Earth Science, 2023)
Shear friction is an important deformation process in tectonically deformed coals (TDCs) and is closely related to the dynamic metamorphism of coal. In the current study, we perform a molecular dynamics (MD) simulation of the shear friction process on primary structure coal. The simulation results show that coal friction is a process of energy transformation. The mechanical energy of shear friction work can lead to temperature increases and chain motion. Chain diffusion and reorientation are the two main chain motion modes during friction. Chain diffusion behavior is regular in the initial friction stage and becomes irregular in the later friction stage. The orientation change is different for various fused aromatic chains. The orientation changes of pentacenes and naphthacenes are more significant than the other fused aromatic chains, indicating that fused aromatic chains with a higher aspect ratio are preferentially reorientated by shear friction. Furthermore, it is also demonstrated that the C-O and C-N bonds in coal are more easily disassociated by shear friction. The research results directly confirm the molecular evolution during coal friction and reveal the evolutionary mechanism of coal molecules caused by shear stress.